DIGITALISASI DALAM PEMBELAJARAN KITAB KUNING METODE BANDONGAN DI PONDOK PUTERI PESANTREN ZAINUL HASAN. - Fauziyah, Rizqi; Alvianti, Dewi; Kamilah, Saifiyatil (Kalam Nusantara Institute, 2024)
The aim of this community service program is to develop Islamic boarding school education in the Karangbong village area, Pajarrakan sub-district, Probolinggo district, so that they can carry out learning productively, effectively and efficiently, so that they can become independent students. Another specific aim is to help create comfort in learning through digital-based yellow book learning activities. The expected output target in this activity is that target partners can understand the advantages and benefits of using digital media in traditional yellow book learning to make it easier to understand. Apart from that, this service program aims to take advantage of the development of digital media which is able to improve students' learning outcomes and interest, especially in the classic bandongan method which must be preserved and able to compete with other forms of learning. Therefore, the method applied is an Asset Based Community Development (ABCD) approach, namely an empowerment of the community using assets. This approach is based on utilizing assets and potential. This activity was carried out at the girls' cottage at the Zainul Hasan Islamic Boarding School. The results of the service show that the Islamic boarding school, which is a partner in empowering the community, has assets that can be developed and optimized with the aim of improving the quality of the yellow book learning activities to produce students who understand religious learning through bandongan method yellow book recitation activities on a digital basis. Basically, the central girls' boarding school has preparations and equipment to facilitate digital-based activities. Through the assistance we provide, the central daughter boarding school is able to map its assets so that it becomes a trigger factor for optimizing its assets, including human resource assets, social networks, physical assets and traditions.